Regional Government Authority in Digital Tourism Development: A Case Study on the Big Farmer Tourist Attraction - Susilawati, Susilawati; Wawat Setiawati (Yayasan Cahaya Generasi Positif, 2025)
This study examines the constitutional and statutory authority of regional governments in Indonesia to develop digital tourism, using the Rimbun Conservation Village in South Tangerang as a case study. Under Law No. 10 of 2009 on Tourism and Regional Regulation No. 5 of 2022, district and municipal governments are empowered to formulate tourism master plans, designate local attractions, regulate operations, and facilitate digital promotion. Employing a normative‐juridical approach combined with qualitative case analysis, this research reviews national and regional legislation and integrates in‐depth interviews with local tourism officials and program reports. Findings reveal that the South Tangerang City Government effectively translated its legal mandate into concrete initiatives by embedding “digital” and “community‐based” tourism objectives into local bylaws, investing in digital infrastructure, and leveraging public–private partnerships such as the Green Camp 2024 collaboration. The digitalization of marketing, virtual tours, and e‐commerce platforms significantly enhanced local income streams, increased participation of micro, small, and medium enterprises (MSMEs), and generated employment within agritourism activities. However, implementation challenges persist, notably digital literacy gaps, uneven internet access, and infrastructure deficits. The study concludes that, while robust legal frameworks provide a solid foundation for digital tourism development, sustainable outcomes depend on ongoing investment in digital capacity building and inclusive policymaking. Recommendations include strengthening digital literacy programs, expanding broadband connectivity, and fostering multi‐stakeholder governance to ensure equitable economic benefits. This research contributes to administrative law scholarship by demonstrating how proactive local legislation and collaborative governance can align statutory authority with innovation in the digital tourism sector.